2015
DOI: 10.14814/phy2.12386
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antecedent moderate-intensity exercise on the glycemia-increasing effect of a 30-sec maximal sprint: a sex comparison

Abstract: This study investigated whether a prior bout of moderate-intensity exercise attenuates the glycemia-increasing effect of a maximal 30-sec sprint. A secondary aim was to determine whether the effect of antecedent exercise on the glucoregulatory response to sprinting is affected by sex. Participants (men n = 8; women n = 7) were tested on two occasions during which they either rested (CON) or cycled for 60-min at a moderate intensity of ~65% (EX) before performing a 30-sec maximal cycling effort 195 min later. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…A study by Davis et al (2000b) reported a similar increase in plasma glucagon in both sexes following 90 minutes of continuous submaximal exercise on a cycle ergometer at 80% of anaerobic threshold (Davis et al 2000b). Similar results were also reported in a study by Justice et al (2015), in which, after repeated bouts of high intensity sprints, there was no main effect of sex on changes in plasma glucagon concentrations (Justice et al 2015). However, other studies have reported a lower glucagon response to exercise in females compared to males exercising on a cycle ergometer at ~50% VO 2 max (Perreault et al 2004;Horton et al 2006a;Tarnopolsky et al 1990;Henderson et al 2008).…”
Section: Individuals Without Diabetessupporting
confidence: 81%
See 4 more Smart Citations
“…A study by Davis et al (2000b) reported a similar increase in plasma glucagon in both sexes following 90 minutes of continuous submaximal exercise on a cycle ergometer at 80% of anaerobic threshold (Davis et al 2000b). Similar results were also reported in a study by Justice et al (2015), in which, after repeated bouts of high intensity sprints, there was no main effect of sex on changes in plasma glucagon concentrations (Justice et al 2015). However, other studies have reported a lower glucagon response to exercise in females compared to males exercising on a cycle ergometer at ~50% VO 2 max (Perreault et al 2004;Horton et al 2006a;Tarnopolsky et al 1990;Henderson et al 2008).…”
Section: Individuals Without Diabetessupporting
confidence: 81%
“…While there are studies that report no sex-related differences in catecholamine response to a Wingate test (30-s maximum sprint on a cycle ergometer) in recreationally active individuals (Vincent et al 2004), and to 14 minutes of anaerobic exercise to exhaustion in moderately trained individuals (Marliss et al 2000), the majority of studies report a significantly greater catecholamine response to various types of exercise in males compared to females (Amiel et al 1993;Gratas-Delamarche et al 1994;Horton et al 1998;Davis et al 2000b;Pullinen et al 2002;Hedrington and Davis 2015;Justice et al 2015). Davis et al (2000b) matched men and women for age, BMI, fitness level and fat mass and found significantly elevated epinephrine and norepinephrine concentrations in men compared to women during moderate aerobic exercise on a cycle ergometer in the fasted state (Davis et al 2000b).…”
Section: Individuals Without Diabetesmentioning
confidence: 99%
See 3 more Smart Citations